2007
DOI: 10.1074/jbc.m609360200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for Co-chaperone Fkbp52 but Not Fkbp51 in Androgen Receptor-mediated Signaling and Physiology

Abstract: Androgen receptor (AR)3 is a hormone-induced transcription factor that controls male sexual development and other important physiologies. Similar to other members of the nuclear receptor family (1, 2), AR has three major functional domains: an N-terminal transactivation domain, a DNA-binding domain, and a C-terminal ligand-binding domain (3-5). Mutations found in each of these domains lead to a series of AR functional defects associated with androgen insensitivity syndrome (AIS) or partial AIS in humans (6, 7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
174
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(181 citation statements)
references
References 59 publications
6
174
1
Order By: Relevance
“…Alcohol-naive adult male and female Fkbp5 knockout (KO) and litter mate wild-type (WT) mice were used. These mice were generated through mating of heterozygous Fkbp5 mice as described in the previous report (Yong et al, 2007). KO mice used for this experiment have been backcrossed with C57BL/6J for four generations.…”
Section: Mouse Experimentsmentioning
confidence: 99%
“…Alcohol-naive adult male and female Fkbp5 knockout (KO) and litter mate wild-type (WT) mice were used. These mice were generated through mating of heterozygous Fkbp5 mice as described in the previous report (Yong et al, 2007). KO mice used for this experiment have been backcrossed with C57BL/6J for four generations.…”
Section: Mouse Experimentsmentioning
confidence: 99%
“…The 52 kDa FK506 binding protein (FKBP52) associates with receptor-Hsp90 complexes by way of a C-terminal TPR domain and is a specific positive regulator of AR, glucocorticoid receptor (GR), and progesterone receptor (PR) signaling (3)(4)(5). FKBP52 is required for normal male sexual differentiation and development in mice as the fkbp52-deficient mice (52KO) display characteristics of partial androgen insensitivity syndrome including dysgenic prostate (4,6). FKBP proteins are validated targets of immunosuppressive drugs.…”
mentioning
confidence: 99%
“…Fkbp52-deficient Mice-Fkbp52-deficient mice were generated as described previously (9). They were maintained in a C57BL/6J/129SvEv mixed background.…”
Section: Methodsmentioning
confidence: 99%
“…Fkbp52 and Fkbp51 are the best known of several tetratricopeptide repeat proteins that co-chaperone steroid receptors, including AR, progesterone receptor, and glucocorticoid receptor (6 -8). Prior work has shown that hypospadias is one of the major physiological defects found in Fkbp52-deficient male mice, but not in Fkbp51-deficient males (9,10). Initial characterization also demonstrated reduced AR-mediated activity when heterologous reporter constructs were transfected into Fkbp52-deficient MEF cells (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation